Semi-automated contact tracing and management of contact precautions during the COVID-19 pandemic within a tertiary hospital. Issue 1 (March 2023) - Bechmann, Lukas; Geginat, Gernot
Summary: Background: Evaluation of a spreadsheet-based COVID-19 contact-tracing tool (CTT) and determination of risk factors for SARS-CoV-2 transmission among hospital staff members. Design: Observational descriptive study on the application and acceptance of the CTT. Retrospective case-control study for SARS-CoV-2 transmission risk factor determination and for evaluation of the CTT's risk stratification algorithm. Setting : Tertiary hospital in Germany. Participants: 3514 contacts of hospital staff members to 322 SARS-CoV-2-positive cases. Methods: A case-control study was performed to identify risk factors for SARS-CoV-2 transmission and for unprotected contacts among staff members. To evaluate strengths and weaknesses of the CTT performance statistics were analyzed and users completed a questionnaire measuring satisfaction and acceptance of the tool. Results: In 2021, the CTT was used for the algorithm-based semi-automated management of 3514 in-hospital contacts. The tool determined the risk category of individual contacts and generated messages for the information of the local public health department, the in-hospital SARS-CoV-2 test center and all staff members who had contact to the index case. Staff members without regular contacts to patients had significantly ( P <0.005) more unprotected contacts to other staff members (25.5% vs. 9.6%) and more SARS-CoV-2 transmissions per contact (4.9% vs. 0.6%) than staff members with frequent contacts to patients. The profession "nurse or medical technical service" was associated with significantly ( P <0.005) more unprotected contacts between staff members (11.0% vs. 2.6%) compared to the profession "physician". Conclusions: Digital tools can increase the efficiency of in-hospital contact tracing. The CTT enable a timely systematic analysis of risk factors among staff members.